Computed tomography angiography with pulmonary artery thrombus burden and right-to-left ventricular diameter ratio after pulmonary embolism. (February 2017) - Ouriel, Kenneth; Ouriel, Richard L; Lim, Yeun J; Piazza, Gregory; Goldhaber, Samuel Z
Purpose: Computed tomography angiography is used for quantifying the significance of pulmonary embolism, but its reliability has not been well defined. Methods: The study cohort comprised 10 patients randomly selected from a 150-patient prospective trial of ultrasound-facilitated fibrinolysis for acute pulmonary embolism. Four reviewers independently evaluated the right-to-left ventricular diameter ratios using the standard multiplanar reformatted technique and a simplified (axial) method, and thrombus burden with the standard modified Miller score and a new, refined Miller scoring system. Results: The intraclass correlation coefficient for intra-observer variability was .949 and .970 for the multiplanar reformatted and axial methods for estimating right-to-left ventricular ratios, respectively. Inter-observer agreement was high and similar for the two methods, with intraclass correlation coefficient of .969 and .976. The modified Miller score had good intra-observer agreement (intraclass correlation coefficient .820) and was similar to the refined Miller method (intraclass correlation coefficient .883) for estimating thrombus burden. Inter-observer agreement was also comparable between the techniques, with intraclass correlation coefficient of .829 and .914 for the modified Miller and refined Miller methods. Conclusions: The reliability of computed tomography angiography for pulmonary embolism was excellent for the axial and multiplanar reformatted methods for quantifying the right-to-left ventricular ratio and for the modified Miller and refined Miller scores for quantifying of pulmonary artery thrombus burden.